Photobody Localization of Phytochrome B Is Tightly Correlated with Prolonged and Light-Dependent Inhibition of Hypocotyl Elongation in the Dark. Issue 2 (25th April 2014) - Van Buskirk, Elise K.; Reddy, Amit K.; Nagatani, Akira; Chen, Meng
Abstract : Photobody localization of Arabidopsis phytochrome B is tightly correlated with the degradation of a phytochrome-interacting factor and the inhibition of hypocotyl growth in the dark. Abstract: Photobody localization of Arabidopsis ( Arabidopsis thaliana ) phytochrome B (phyB) fused to green fluorescent protein (PBG) correlates closely with the photoinhibition of hypocotyl elongation. However, the amino-terminal half of phyB fused to green fluorescent protein (NGB) is hypersensitive to light despite its inability to localize to photobodies. Therefore, the significance of photobodies in regulating hypocotyl growth remains debatable. Accumulating evidence indicates that under diurnal conditions, photoactivated phyB persists into darkness to inhibit hypocotyl elongation. Here, we examine whether photobodies are involved in inhibiting hypocotyl growth in darkness by comparing the PBG and NGB lines after the red light-to-dark transition. Surprisingly, after the transition from 10 μmol m −2 s −1 red light to darkness, PBG inhibits hypocotyl elongation three times longer than NGB . The disassembly of photobodies in PBG hypocotyl nuclei correlates tightly with the accumulation of the growth-promoting transcription factor PHYTOCHROME-INTERACTING FACTOR3 (PIF3). Destabilizing photobodies by either decreasing the light intensity or adding monochromatic far-red light treatment before the light-to-dark transition leads to faster PIF3 accumulation and a dramatic reduction in the capacity for hypocotyl growth inhibition in PBG . In contrast, NGB is defective in PIF3 degradation, and its hypocotyl growth in the dark is nearly unresponsive to changes in light conditions. Together, our results support the model that photobodies are required for the prolonged, light-dependent inhibition of hypocotyl elongation in the dark by repressing PIF3 accumulation and by stabilizing the far-red light-absorbing form of phyB. Our study suggests that photobody localization patterns of phyB could serve as instructive cues that control light-dependent photomorphogenetic responses in the dark.